Early implantation of multiple spring coils for severe haemolysis after incomplete transcatheter occlusion of persistent arterial duct. - Cheung, Y. F. (1997)
An 18 month old girl with an angiographically measured ductus of 4.5 mm underwent transcatheter occlusion of the persistent arterial duct with a 17 mm Rashkind umbrella and an occluding spring coil. Severe intravascular haemolysis developed 20 hours later. Significant residual ductal leakage was noted and the residual duct measured 6 mm. Previous underestimation might have been related to ductal spasm as a catheter was placed across the duct before angiography. The haemolysis was abolished within 48 hours by a previously unreported approach of antegrade transcatheter closure of the residual duct by multiple spring coils.